Economic, Political, Social Factor of Corruption in the Slovak Republic - Merickova, Beata Mikusova; Bastekova, Andrea; Stejskal, Jan; Pekar, Bernard (My University, 2017)
Interdisciplinary defi nitions of corruption perceive corrupt actions as contrary to legal and ethical standards aff ecting the public interest, perpetrated by a person in public offi ce. Th e main goal of the study is to identify the factors of corrupt acts in the public sector stemming from the economic, political, cultural and social environments in the Slovak Republic. Th rough the Delphi method we verify the relevance of economic, political and cultural-social factors of corrupt acts in the public sector defi ned in the theoretical framework of this issue. Th e Delphi method was used under the following conditions: the anonymity of experts, feedback control and statistical determination of a consensus of experts. Expert evaluation of the factors underlying corrupt behaviour in the public sector enabled us not only to detect the overall relevance of the factors, but also to identify areas where corruption in the public sector is most widespread, according to experts. We can state that the most problematic areas include the judiciary and the police.
Ekonomické, politické a sociální faktory korupce ve Slovenské republice
Keywords: Corruption definition; public sector; Delphi method; economic factor of corruption; political factor of corruption; social factor of corruption; korupce; veřejný sektor; Delfská metoda; ekonomické faktory korupce; politické faktory korupce